2006
DOI: 10.1152/japplphysiol.00571.2005
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism during prolonged exercise and recovery: interactions between pyruvate dehydrogenase, fatty acids, and amino acids

Abstract: Mourtzakis, Marina, Bengt Saltin, Terry Graham, and Henriette Pilegaard. Carbohydrate metabolism during prolonged exercise and recovery: interactions between pyruvate dehydrogenase, fatty acids, and amino acids. J Appl Physiol 100: 1822-1830, 2006. First published January 19, 2006 doi:10.1152/japplphysiol.00571.2005.-During prolonged exercise, carbohydrate oxidation may result from decreased pyruvate production and increased fatty acid supply and ultimately lead to reduced pyruvate dehydrogenase (PDH) activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
38
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 39 publications
7
38
1
Order By: Relevance
“…Previous studies have demonstrated that PGC-1␣ regulates hepatic glucose metabolism by inducing expression of gluconeogenic genes (32)(33)(34)53). Gluconeogenesis is an important source of glucose for skeletal muscle, especially during periods of exertional activity (54). Several lines of evidence shown here support the conclusion that PGC-1␣ also exerts regulatory action directly on muscle to increase glucose availability by augmenting glycogen stores post-exercise through stimulation of glucose import and via "glycogen sparing" effects (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have demonstrated that PGC-1␣ regulates hepatic glucose metabolism by inducing expression of gluconeogenic genes (32)(33)(34)53). Gluconeogenesis is an important source of glucose for skeletal muscle, especially during periods of exertional activity (54). Several lines of evidence shown here support the conclusion that PGC-1␣ also exerts regulatory action directly on muscle to increase glucose availability by augmenting glycogen stores post-exercise through stimulation of glucose import and via "glycogen sparing" effects (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, 82 discrepancies within these human studies, including B-vitamin and subject training status, as 83 well as variations in mode, intensity, and duration of test exercises, limit the strength of their 84 conclusions [16,17]. Mechanistically, reductions in homocysteine concentrations by exercise 85 may be related to increased protein turnover owing to increased plasma methionine 86 concentrations during exercise, followed by reduced concentrations below basal levels after 87 exercise [18][19][20][21]. This fluctuation in methionine availability for methyl group metabolism may 88 be due, in part, to the increased need of methionine for muscle anabolism, potentially resulting in 89 diminished homocysteine production [17,21].…”
mentioning
confidence: 99%
“…Mechanistically, reductions in homocysteine concentrations by exercise 85 may be related to increased protein turnover owing to increased plasma methionine 86 concentrations during exercise, followed by reduced concentrations below basal levels after 87 exercise [18][19][20][21]. This fluctuation in methionine availability for methyl group metabolism may 88 be due, in part, to the increased need of methionine for muscle anabolism, potentially resulting in 89 diminished homocysteine production [17,21]. However, exercise also increases the demand of 90 vitamin B6 to support increased muscle catabolism, thereby potentially limiting its availability 91 for transsulfuration and subsequently resulting in homocysteine accumulation [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some amino acids have important implications for gluconeogenesis and nitrogen balance during and following exercise. Glutamine, glutamate and alanine are gluconeogenic precursors that interlink with pyruvate metabolism and are therefore essential to carbohydrate metabolism (2). An extensive discussion of protein metabolism at rest and during exercise is beyond the scope of this project and for this reason the following chapters will focus only on the contribution of carbohydrate and fat to energy expenditure during and following exercise and the metabolic pathways regulating each.…”
Section: Macronutrients For Energy Productionmentioning
confidence: 99%